Understanding Osteoporosis: A Comprehensive Review of Risk Factors, Mechanisms, and Management Strategies - S. Saranya (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Osteoporosis is a systemic skeletal disorder characterized by decreased bone density and micro architectural deterioration, leading to an increased risk of fractures and significant morbidity and mortality. This review provides a comprehensive overview of osteoporosis, focusing on its epidemiology, pathophysiology, risk factors, clinical manifestations, diagnosis, and management strategies. Risk factors for osteoporosis include age, gender, genetics, hormonal factors, lifestyle factors, medication use, and comorbidities. The pathophysiology involves an imbalance between bone resorption and formation, primarily driven by alterations in osteoblast and osteoclast activity, along with various regulatory factors. Diagnostic approaches such as bone mineral density measurement and fracture risk assessment tools are essential for early detection and risk stratification. Management strategies include lifestyle modifications, pharmacological interventions, and fall prevention strategies aimed at reducing fracture risk and improving quality of life in patients with osteoporosis. This review highlights the importance of a multidisciplinary approach involving healthcare professionals, patients, and caregivers in the prevention, diagnosis, and management of osteoporosis to minimize its burden on individuals and healthcare systems